The Analysis Effect of International Price, GDP, Land Area and Substitutional Price on Export Volume of Indonesian Palm Oil - Uli Wildan Nuryanto; Silvia Ekasari; Muhammad Asir; Mihel Tuatfaru; Ferly Agustina Sairmaly (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The objective of this study is determine and analyse effect of international price, GDP, land area and substitutional price on export volume of Indonesian Palm Oil. The data that the authors use in this study are secondary data types in the form of a 33-year time series, starting in 1986-2018. Secondary data were obtained from the Central Bureau of Statistics, the Directorate General of Plantations, the World Bank, UN Comtrade, the IMF, the US Department of Agriculture, several literatures, and sites related to research. The data analysis that the authors used in this study was by using the Error Correction Model (ECM) method with the analysis tool used to process the data, namely eviews 8. In this study, the data were obtained by means of documentation, namely, data collection was carried out in the classification category of written data that related to research problems from various sources, including books, journals, and existing publication websites. The conclusion from this study is that the variable land area has a significant positive effect on the volume of Indonesian palm oil exports to India for the 1986–2018 period in the short and long term. This result is in accordance with the hypothesized hypothesis. International price variables have a significant negative effect on the volume of Indonesian palm oil exports to India for the 1986–2018 period in both the short and long terms.